(3TQM NdGUI GdMSGHs - (3Ydj Hf GdMSfj GdNdNGdis; (3HgGA GdOjf eMeO Hf MSjf GdMGQKj GdgeOGfj GdTjYj GdYGedj,J (B1031 (3g` s
(3ChdgG (B:s
(3Cf GcJH TQMkG LGeYkG dgG ai GdQSGdI GdeQSheI HNdGUI GdMSGHI GdefShHI Edi GdESJGP GdeMbb HgGA GdOjf eMeO Hf MSjf s
(3BNQgG (B:s
(3Je CYde CjgG GdCN GdCN GdCeLO deG cGf ZQV GdeUfa ef hVY gPg GdQSGdI GdTQjaI JdNjU bhGYO GdMSGH GdMeO ddg Ydi NJe GdcJGH s
(3GdNdGUI ai GdMSGH GfXQ cTa GdXfhf L (B1 (3U` (B720s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B102s
Keywords: (3GdQjGVjGJs